Fracture Toughness in Advanced Materials: A Comparative Review of Testing Methods and Standards - Abhasika Bahre (International Journal of Fracture Mechanics and Damage Science, 2025)
Fracture toughness is a key material property used to assess a material's ability to resist crack propagation, which is vital for ensuring the reliability and durability of structures and components in high-performance applications. It is particularly important in advanced materials such as composites, ceramics, and high-strength alloys, which are increasingly used in demanding industries such as aerospace, automotive, and civil engineering. Fracture toughness testing helps determine the material's behavior under stress and predicts its performance in real-world applications, where cracks or defects could lead to catastrophic failure. This paper offers a thorough review of the various testing methods and international standards used to measure fracture toughness in advanced materials. It critically analyzes both traditional and modern testing techniques, examining their advantages, limitations, and suitability for different materials and applications. By evaluating well-established methods like Linear Elastic Fracture Mechanics (LEFM) and Elastic-Plastic Fracture Mechanics (EPFM), as well as newer techniques such as micro-scale testing and digital image correlation, the review provides a comprehensive understanding of the diverse approaches used to assess fracture toughness. Additionally, the review compares international testing standards, including ASTM, ISO, and other globally recognized protocols. These standards offer guidelines on specimen preparation, test conditions, and data interpretation, ensuring consistency and reliability in fracture toughness measurements. By comparing these standards, the paper identifies the commonalities and differences that impact their applicability to different material types and testing environments. This comparative analysis ultimately seeks to establish a unified framework for fracture toughness testing, ensuring that the results are relevant, reproducible, and adaptable to modern engineering requirements. The review concludes by highlighting the importance of continuous advancements in fracture toughness testing methods to keep pace with innovations in material science.
Keywords: J-integral; advanced materials; digital image correlation; fracture toughness; micro-scale testing; standards; stress intensity factor; testing methods